Socio-economic factors influencing attitude of Sabah oil palm smallholders in dealing with ganoderma basal stem rot disease - Siti Kalsom Yulo; Abdul Rahim Awang; Markus Atong; Bonaventure Boniface; Mohammad Amizi Ayob; Nur Izzaty Iqlima Norazman; Assis Kamu (AENSI Publisher, 2015)
The main focus of this paper was to determine the relationships between the socio-economic background of Sabah’s oil palm smallholders and their attitude in dealing with Ganoderma Basal Stem Rot (BSR) disease. A multistage random sampling using a structured questionnaire was used to obtain the data from 500 oil palm smallholders in nineteen different districts in Sabah. Based on the factor analysis on the attitude towards Ganoderma disease, respondents indicated that they knew the causes of the disease infection. But in terms of disease management, such as, treatment and preventive measures, their exposure to information was limited, while at the same time they were facing constraints in dealing with the disease. The study findings showed that there were significant relationships between socio-economic background and attitude of the oil palm smallholders in terms of category of smallholders, gender, level of education and years of experience in oil palm cultivation. The existing relevant agencies in Sabah, such as, the Malaysia Palm Oil Board (MPOB), Sabah State Department of Agriculture and Former Association should step up their efforts to provide better information and create more awareness among oil palm smallholders about the disease, and to really convince them about its devastating economic and social impacts. Comprehensive trainings in managing the disease should be conducted, giving priorities to controlling the disease through more affordable and less burdensome, but more effective methods.